IMPLEMENTASI JARINGAN ENTERPRISE UNTUK MENINGKATKAN AVAILABILITY JARINGAN (Study Kasus di SMK N 2 Yogyakarta) - Haryanto . (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2017)
The enterprise network is a small, medium, or large-scale network in which there is a system built to meet the needs of internal users in accessing intranet, extranet, and remote systems applications. Network availability can be improved by applying redundant networks and hierarchical networks. Redundant links function as fault tolerant when there are links or networking devices that do not work. The purpose of this research is to replace the topology tree network with enterprise network. Implementation of enterprise network in SMK N 2 Yogyakarta is designed in accordance with the needs of school networks. Enterprise networks implement VLAN and RSTP (Rapid Spanning Tree Protocol). The network is implemented by adding core layer and distribution layer while the access layer is fixed. At core layer and distribution layer apply redundant link by using Rapid Spanning Tree Protocol. From the results of implementation and testing proved that network availability increased by applying redundant links.